RELATIONSHIP OF WATER AND WATER RESERVOIRS WITH THE PRESENCE OF AEDES AEGYPTI LARVAE IN PUUWATU PUBLIC HEALTH CENTER WORKING AREA KENDARI CITY: Water and water reservoirs with Aedes Aegypti - Titi Saparina L; Noviati Noviati (STIKes Mandala Waluya Kendari, 2020)
Background: Aedes aegypti mosquitoes like to put their eggs in clean water so it is necessary to pay attention to the condition of the shelter of the water to always be closed because the water reservoir is in a closed condition it is less likely for the larvae to breed. Based on observation of 5 patient's house got mosquito larvae at water reservoir, other than that water reservoir left open and water quality slippery. This study aims to determine the relationship between water and aqueduct collection in the presence of Aedes aegypti larvae in the Work Area of ??Puuwatu Health Centre inKendari. Methods:This type of research is a quantitative research with cross sectional study approach. The population is 265 and the sample is 72 respondents using random sampling technique Results:The results in this study indicate that the statistical water storage test results X2 count 36.217 > X2 table 3.841 and water channel value X2 count 16,774 > X2 table 3,841. So it is concluded that there is a connection of water reservoirs and waterways with the presence of Aedes aegypti larvae in the Work Area of ??Puuwatu Health Centre in Kendari. Conclusion: Suggested to the family should pay attention to environmental sanitation that can provide breeding place mosquito larvae breeding such as water and water ditch. In addition, the family must adjust the area of ??the house with the number of occupants in the house.